A single nucleotide polymorphism in an IgA1 protease gene determines Streptococcus pneumoniae adaptation to the middle ear during otitis media. Issue 1 (10th December 2020) - Tikhomirova, Alexandra; Trappetti, Claudia; Paton, James C; Watson-Haigh, Nathan; Wabnitz, David; Jervis-Bardy, Jake; Jardeleza, Camille; Kidd, Stephen P
ABSTRACT: Factors facilitating the chronicity of otitis media (OM) in children are, to date, not fully understood. An understanding of molecular factors aiding bacterial persistence within the middle ear during OM could reveal pathways required for disease. This study performed a detailed analysis of Streptococcus pneumoniae populations isolated from the nasopharynx and middle ear of one OM case. Isolates were assessed for growth in vitro and infection in a mouse intranasal challenge model. Whole genome sequencing was performed to compare the nasopharyngeal and middle ear isolates. The middle ear isolate displayed a reduced rate of growth and enhanced potential to transit to the middle ear in a murine model. The middle ear population possessed a single nucleotide polymorphism (SNP) in the IgA1 protease gene igA, predicted to render its product non-functional. Allelic exchange mutagenesis of the igA alleles from the genetic variant middle ear and nasopharyngeal isolates was able to reverse the niche-adaptation phenotype in the murine model. These results indicate the potential role of a SNP in the gene encoding the IgA1 protease, in determining S. pneumoniae adaptation to the middle ear during chronic OM. In contrast, a functional IgA1 protease was associated with increased colonisation of the nasopharynx. Abstract : Identification of IgA1 protease genetic variants of Streptococcus pneumoniae isolated from the nasopharynx and middle ear.